Constitutional protection of Egyptian women’s rights in personal affairs - Aliaa Zakaria; Alaa Abouahmed (Cogent Social Sciences)
This article addresses various controversial issues relevant to the status of Egyptian women in personal affairs, specifically the validity of customary marriage and divorce, the implications of Khul’, and the wife’s right to file for divorce in case of her husband’s remarriage to another woman. By critically examining these matters, the article aims to shed light on the challenges faced by Egyptian women and advocate for necessary reforms. The article delves into the legal intricacies and social implications of customary marriage, highlighting the absence of official recognition and its adverse effects on women’s rights. It analyzes the role of Khul’, the financial settlement made by the wife to obtain a divorce, and explores its impact on the wife’s economic autonomy. By shedding light on these issues, the article advocates reforming the customary marriage system, providing equitable financial settlements, and safeguarding women’s right to divorce. It emphasizes the urgency of legal and societal changes to address the systemic disadvantages faced by Egyptian women in personal affairs. The findings provide valuable insights for policymakers, legal practitioners, and advocates striving for gender equality and social justice in Egypt.